Photo-oxidation efficient As (III) under visible light using microporous Zn doped-Fe3O4 sphere. (11th May 2020) - Nguyen, Xuan Sang; Pham, Tien Dung; Tran, Trang Thu Thi; Tung Vo, Hoang
ABSTRACT: A series of microporous Zn doped Fe3 O4 spheres were successfully fabricated by a simple method. The characteristic of the obtained products was studied using the X-ray diffraction (XRD), Raman spectroscopy, (SEM) scanning electron microscopy, UV-vis reflectance, FTIR techniques. The photo-oxidation of As(III) to As(V) by as-synthesised samples under visible light was examined. The results exposed that with Zn doped Fe3 O4 photocatalyst, the complete oxidation of As(III) to As(V) was observed, in which 1.05% mol of Zn doped into Fe3 O4 showed the best photocatalytic performance. The proposed mechanism of photocatalytic activity enhancement was also investigated, indicating the introduction Zn content act as a trapping electron-centre resulting in the decreasing in the recombination rate of the photogenerated electron/hole pairs thus improving the photocatalytic performance. Photocatalytic tests were presented also in real groundwater and complete oxidation of As(III) to As(V) by 1.05 Zn doped Fe3 O4 photocatalyst was achieved in 180 min under visible light irradiation.